2021
DOI: 10.3171/case21401
|View full text |Cite
|
Sign up to set email alerts
|

Successful multiple burr hole openings for limb-shaking transient ischemic attack due to moyamoya disease: illustrative case

Abstract: BACKGROUND Limb-shaking transient ischemic attacks (LS-TIAs) are a rare form of TIAs that present as involuntary movements of the limbs and indicate severe cerebral hypoperfusion. LS-TIAs are often reported in patients with carotid artery stenosis but can also affect patients with intracranial artery stenosis and moyamoya disease (MMD). OBSERVATIONS A 72-year-old woman presented with repeated episodes of involuntary shaking movements of the right upper limb. Cerebral angiography revealed complete occlusion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…A total of 82 reports containing 161 cases that developed limb-shaking TIA from 25 countries were reported (Supplementary Material 2, Supplemental Digital Content 1, http://links.lww.com/NRL/A122). 6–87 The origin was European in 63 cases, Asian in 56, North American in 38, South American in 3, and 1 Australian. Figure 2 shows the number of articles published about limb-shaking TIA over time.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 82 reports containing 161 cases that developed limb-shaking TIA from 25 countries were reported (Supplementary Material 2, Supplemental Digital Content 1, http://links.lww.com/NRL/A122). 6–87 The origin was European in 63 cases, Asian in 56, North American in 38, South American in 3, and 1 Australian. Figure 2 shows the number of articles published about limb-shaking TIA over time.…”
Section: Resultsmentioning
confidence: 99%
“…In 2009, Turtzo et al reported the second case treated with angioplasty and stenting, which had good outcomes 41 . In 2021, Ikeuchi et al described a case in which conservative, bypass, and synangiosis therapies failed 80 . The authors attempted multiple burr hole openings with improvement in motor symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation